Accessibility of Cities in the Digital Economy - Emmanouil Tranos; Aura Reggiani; Peter Nijkamp (Tinbergen Institute, 2013)
This paper introduces a new measure to approach the accessibility of places in the frame of the digital economy. Information and Communication Technologies (ICTs) and the Internet are not equally spread around places and this heterogeneity affects spatial configuration. Despite the wide societal changes due to ICTs and the extensive interest in accessibility studies, these two themes have not yet come together in order to study the digital accessibility (DA) of places. Adopting an infrastructural perspective and a potential accessibility framework, a DA measure â exteuro“ embedding different types of impedance distance functions â exteuro“ is calculated for cities in Europe. Spatial Interaction Model and Complex Network Analysis are employed to calibrate and validate the DA results. The outcome of this approach is a new urban hierarchy which reveals a core-periphery pattern in Europe owing to digital accessibility.
Keywords: O1; L63; 330; digital accessibility; Internet geography; potential accessibility; impedance functions